Hospital Readiness for Covid 19 Pandemic in Bekasi District Hospital - Arda Yunita; Wiku Bakti Bawono Adisasmito (Universitas Muhammadiyah Semarang, 2022)
Background: In the beginning of Covid-19 pandemic, most of hospitals were unplanned to handle this pandemic. The purpose of this study’s are to analyze the hospital readiness to cope with pandemic circumstances by evaluating hospital strategies as well as action which implement by the hospital. Methods: The study employs a method approach that includes both mix quantitative and qualitative methods. Quantitative design use main data while score and percentage as an outcome of response from checklist based on WHO Rapid Hospital Readiness as a quantitative study supported with qualitative study by in-depth interview utilize response from 12 different components on the checklist. Measurement of Hospital Readiness was carried out in Bekasi District Hospital and responses were obtained three times within seven months duration. Results: The results are as follows, first period as a baseline data in December 2020, the average score assessed is 69%, second period were taken on April 2021 average score slightly improve to 81% and the last period in July 2021 result increased to 90%. In the last period among other component, Component 10 have the lowest percentages (60%). By accomplishing the strategy for each period and continuously evaluated, the score or percentage by assessment of surge capacity readiness due to the Covid-19 pandemic has increased in Bekasi District Hospital, indicating the hospital is more ready to deal with surge capacity, and hospital perseverance is good enough. Conclusion: The checklist of the hospital readiness can be used as a baseline and a tool for hospital and health facilities evaluation.